Beispiel Nr: 48
$ \text{Gegeben:} y=ax^2+bx+c \\ \text{Gesucht:} \\ \text{Scheitel und Scheitelform}\\ \text{Definitions- und Wertebereich} \\ \text{Nullstellen - Schnittpunkt mit der x-Achse} \\ \text{Faktorisiere Form} \\ \text{Scheitel} \\ Eigenschaften\\ \textbf{Gegeben:} \\ y=-1\frac{1}{2}x^2+2x+\frac{1}{3}\\ \\ \textbf{Rechnung:} \\\bullet \text{Funktion} \\ y=-1\frac{1}{2}x^2+2x+\frac{1}{3}\\ \\ \bullet \text{Scheitelberechnung } \\ \begin{array}{l|l|l} \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=-1\frac{1}{2}x^2+2x+\frac{1}{3} \\ y=-1\frac{1}{2}(x^2-1\frac{1}{3}x-\frac{2}{9}) \\ y=-1\frac{1}{2}(x^2-1\frac{1}{3}x+\left(\frac{2}{3}\right)^2-\left(\frac{2}{3}\right)^2-\frac{2}{9}) \\ y=-1\frac{1}{2}[(x-\frac{2}{3})^2-\left(\frac{2}{3}\right)^2-\frac{2}{9}] \\ y=-1\frac{1}{2}[(x-\frac{2}{3})^2-\frac{4}{9}-\frac{2}{9}] \\ y=-1\frac{1}{2}[(x-\frac{2}{3})^2-\frac{2}{3}] \\ y=-1\frac{1}{2}(x-\frac{2}{3})^2+1 \\ Scheitel(\frac{2}{3}/1) \end{array} & \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=-1\frac{1}{2}x^2+2x+\frac{1}{3} \\ y=-1\frac{1}{2}(x^2-1\frac{1}{3}x)+\frac{1}{3} \\ y=-1\frac{1}{2}(x^2-1\frac{1}{3}x+\left(\frac{2}{3}\right)^2-\left(\frac{2}{3}\right)^2)+\frac{1}{3} \\ y=-1\frac{1}{2}[(x-\frac{2}{3})^2-\left(\frac{2}{3}\right)^2]+\frac{1}{3} \\ y=-1\frac{1}{2}[(x-\frac{2}{3})^2-\frac{4}{9}]+\frac{1}{3} \\ y=-1\frac{1}{2}(x-\frac{2}{3})^2+\frac{2}{3}+\frac{1}{3} \\ y=-1\frac{1}{2}(x-\frac{2}{3})^2+1 \\ Scheitel(\frac{2}{3}/1) \end{array} & \begin{array}{l} \text{Scheitelformel} \\ \hline y=-1\frac{1}{2}x^2+2x+\frac{1}{3} \\ xs=-\frac{2}{2\cdot \left(-1\frac{1}{2}\right)} \\ xs=\frac{2}{3} \\ ys=\frac{1}{3}-\frac{2^2}{4\cdot\left(-1\frac{1}{2}\right)} \\ ys=1 \\ Scheitel(\frac{2}{3}/1)\\ y=-1\frac{1}{2}(x-\frac{2}{3})^2+1 \end{array} \\ \end{array} \\ \\ \\\bullet\text{Definitions- und Wertebereich:}\qquad \mathbb{D} = \mathbb{R} \qquad \mathbb{W} = ]-\infty;1]\\ \\=-1\frac{1}{2}(x+0,15)(x-1,48)\\ \\\bullet \text{Nullstellen / Schnittpunkt mit der x-Achse:} \\y=-1\frac{1}{2}x^2+2x+\frac{1}{3} = 0 \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ -1\frac{1}{2}x^{2}+2x+\frac{1}{3} =0 \\ x_{1/2}=\displaystyle\frac{-2 \pm\sqrt{2^{2}-4\cdot \left(-1\frac{1}{2}\right) \cdot \frac{1}{3}}}{2\cdot\left(-1\frac{1}{2}\right)} \\ x_{1/2}=\displaystyle \frac{-2 \pm\sqrt{6}}{-3} \\ x_{1/2}=\displaystyle \frac{-2 \pm2,45}{-3} \\ x_{1}=\displaystyle \frac{-2 +2,45}{-3} \qquad x_{2}=\displaystyle \frac{-2 -2,45}{-3} \\ x_{1}=-0,15 \qquad x_{2}=1,48 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ -1\frac{1}{2}x^{2}+2x+\frac{1}{3} =0 \qquad /:-1\frac{1}{2} \\ x^{2}-1\frac{1}{3}x-\frac{2}{9} =0 \\ x_{1/2}=\displaystyle -\frac{-1\frac{1}{3}}{2}\pm\sqrt{\left(\frac{\left(-1\frac{1}{3}\right)}{2}\right)^2- \left(-\frac{2}{9}\right)} \\ x_{1/2}=\displaystyle \frac{2}{3}\pm\sqrt{\frac{2}{3}} \\ x_{1/2}=\displaystyle \frac{2}{3}\pm0,816 \\ x_{1}=1,48 \qquad x_{2}=-0,15 \end{array}\\ \end{array}\\ \underline{x_1=-0,15; \quad1\text{-fache Nullstelle}} \\\underline{x_2=1,48; \quad1\text{-fache Nullstelle}} \\ \\ \bullet \text{Vorzeichentabelle:} \\ \begin{array}{|c|c|c|c|c|c|c||} \hline & x < &-0,15&< x <&1,48&< x\\ \hline f(x)&-&0&+&0&-\\ \hline \end{array}\\ \\ \underline{\quad x \in ]-0,15;1,48[\quad f(x)>0 \quad \text{oberhalb der x-Achse}}\\ \\ \underline{\quad x \in ]-\infty;-0,15[\quad \cup \quad]1,48;\infty[\quad f(x)<0 \quad \text{unterhalb der x-Achse}}$